2017
DOI: 10.1038/s41531-017-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of influenza and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) can be eliminated by the use of influenza therapeutics: experimental evidence for the multi-hit hypothesis

Abstract: Central Nervous System inflammation has been implicated in neurodegenerative disorders including Parkinson’s disease (Ransohoff, Science 353: 777–783, 2016; Kannarkat et al. J. Parkinsons Dis. 3: 493–514, 2013). Here, we examined if the H1N1 influenza virus (Studahl et al. Drugs 73: 131–158, 2013) could synergize with the parkinsonian toxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (Jackson-Lewis et al. in Mark LeDoux (ed) Movement Disorders: Genetics and Models: 287–306, Elsevier, 2015) to induce a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 22 publications
2
70
0
1
Order By: Relevance
“…30 Studies assessing LPS/viral exposure and PD in animal models assess results over days rather than years. 6,28 Individuals may require multiple hits of severe infection/sepsis to develop α-synucleinopathy. Our study, however, did not demonstrate increased odds of α-synucleinopathy among those hospitalized more than once.…”
Section: Discussionmentioning
confidence: 99%
“…30 Studies assessing LPS/viral exposure and PD in animal models assess results over days rather than years. 6,28 Individuals may require multiple hits of severe infection/sepsis to develop α-synucleinopathy. Our study, however, did not demonstrate increased odds of α-synucleinopathy among those hospitalized more than once.…”
Section: Discussionmentioning
confidence: 99%
“…Model pathogens such as S. typhimurium or M. leprae are certainly of interest for understanding LRRK2 function in a defined context, but from an epidemiological viewpoint these would seem unlikely major initiators of PD or IBD. This in turn raises the question of how LRRK2 may modulate the response to more ubiquitous pathogens implicated in PD and IBD, such as gut microbiota (Houser and Tansey, 2017;Ni et al, 2017), periodontal microbes (Vavricka et al, 2013;Chen et al, 2017) or influenza virus (Sadasivan et al, 2017). This is likely an interesting area of future research.…”
Section: Lrrk2 As a Potential Therapeutic Target For Inflammatory Dismentioning
confidence: 99%
“…Olsen et al [114] also demonstrated that viral neuroinflammatory priming in the substantia nigra significantly exacerbated α-synuclein aggregate-induced neuroinflammation and neurodegeneration. Another group likewise observed an enhanced neurodegenerative effect by combination of the H1N1 influenza virus and MPTP [115]. However, it is not yet known how or if the response differs between different neurodegenerative conditions or different priming agents.…”
Section: Microglial Role In Chronic Neuroinflammation and Neurodegenementioning
confidence: 99%